2017
DOI: 10.1542/peds.2016-3237
|View full text |Cite
|
Sign up to set email alerts
|

Pictograms, Units and Dosing Tools, and Parent Medication Errors: A Randomized Study

Abstract: Provision of dosing tools more closely matched to prescribed dose volumes is an especially promising strategy for reducing pediatric dosing errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 30 publications
2
71
0
Order By: Relevance
“…This requires that all caregivers are adequately trained on how to appropriately administer the medication, despite the fact that only the parent might have been instructed on medication administration by a physician or other medical provider. In addition, use of over-the-counter medications occurs frequently, parents often fail to use standard dosing instruments, and commonly used prescribing terms such as ‘teaspoon’ and ‘tablespoon’ are often confused 24…”
Section: Medication Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires that all caregivers are adequately trained on how to appropriately administer the medication, despite the fact that only the parent might have been instructed on medication administration by a physician or other medical provider. In addition, use of over-the-counter medications occurs frequently, parents often fail to use standard dosing instruments, and commonly used prescribing terms such as ‘teaspoon’ and ‘tablespoon’ are often confused 24…”
Section: Medication Administrationmentioning
confidence: 99%
“…A major focus of this initiative and of paediatric medication safety research is on reducing MAEs through use of standard medication labels and dosing devices. Research has shown that provision of dosing tools that more closely match prescribed dose volumes may be particularly effective for reducing dosing administration errors 24. Because low health literacy is a major risk factor for MAEs, increasing use of pictograms has been promoted.…”
Section: Medication Administrationmentioning
confidence: 99%
“…Another SAFE Rx for Kids experiment investigated additional strategies to reduce dosing errors, with findings published in 2017. 4 Text-plus-pictographic dosing instructions were associated with a twofold reduction in large overdosing errors (>2-fold errors) compared with text-only instructions. Fewer errors were seen when parents measured with tools with a volume capacity more closely matched to the prescribed dose volume; a tool that is much larger than necessary allows room for excess medication, whereas a tool that is smaller than a prescribed dose necessitates the measurement of >1 instrument full.…”
Section: What's Newmentioning
confidence: 93%
“…61 Liquid dosing errors can be addressed with in-office videos, effective measurement devices, teach-back and show-back counseling techniques, and picturebased handouts. 62 Evidence-based clinical practice guidelines can direct care decisions both toward wanted and away from unwanted actions, resulting in reduced opportunities for harm and in improved outcomes. 57 Other safety goals, such as the recognition of a change in a patient's status or encouraging patient and family involvement in the patient's care, require a composite of changes to health care systems and expectations of both providers and consumers.…”
Section: Patient Safety Strategiesmentioning
confidence: 99%